ANALISIS GAYA KONSUMTIF MAHASISWA ILMU EKONOMI UNIMED: NAVIGASI HARGA DAN PROMO E-COMMERCE - Frandika Situmorang; Ainur Oktania; Gresia Septina Sitohang; Nasrullah Hidayat (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to analyze the consumer behavior of Student of Economics in State University of Medan (UNIMED) in interacting with e-commerce platforms, particularly in response to price changes and promotions. The study employed a qualitative approach with descriptive analysis. A sample of 35 respondents was selected purposefully. Data was collected through online questionnaires and analyzed using descriptive analysis. The results show that discounts can influence students' purchasing interest, but not significantly. Students find promotional products with poor quality, so they consider both price and product size, product quality becomes an important aspect in purchasing decisions, and students' purchasing priorities are based on the price of daily necessities. This study ultimately shows that Student of Economics in State University of Medan (UNIMED) have rational and critical consumer behavior in online shopping. They are not only influenced by discounts but also consider their quality and needs.